2022
DOI: 10.1155/2022/1007954
|View full text |Cite|
|
Sign up to set email alerts
|

Realization of Music-Assisted Interactive Teaching System Based on Virtual Reality Technology

Abstract: Virtual reality technology has attracted researchers’ attention because it can provide users with a virtual interactive learning environment. Based on the theory of virtual reality technology, this paper proposes the system model design and architecture of virtual interactive music-assisted interactive teaching and realizes key technologies such as modeling, music-assisted interactive teaching scene interaction, and database access. In the simulation process, based on the VRML/X3D bottom interactive system tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The rise of online education platforms has allowed music education to break through the constraints of time and space, achieving remote teaching and resource sharing [ 61 ]. Meanwhile, Virtual Reality (VR) and Augmented Reality (AR) technologies bring a more vivid, interesting, and interactive experience to music teaching [ 62 ].…”
Section: Section 4: Swot Factor Identificationmentioning
confidence: 99%
“…The rise of online education platforms has allowed music education to break through the constraints of time and space, achieving remote teaching and resource sharing [ 61 ]. Meanwhile, Virtual Reality (VR) and Augmented Reality (AR) technologies bring a more vivid, interesting, and interactive experience to music teaching [ 62 ].…”
Section: Section 4: Swot Factor Identificationmentioning
confidence: 99%
“…Views of the relevance of CT to the improvement of different competencies in second language learners have been noticed by many scholars, adhering to the belief that teachers can play a substantial role in designing a CT curriculum. As researchers recommend, one of the most promising ways to inspire learning CT skills in students would be through the direct involvement of CT skills in the educational framework (Abrami et al, 2008; Gao et al, 2017; Li, 2011; Ramsay, 2009). Infusing CT skills in educational settings could be rewarding as the students tend to improve their social reciprocity, be sensible, and mirror their analytical thinking in their arguments (Zivkovil, 2016).…”
Section: Argumentative Writing Critical Thinking and Language Learnersmentioning
confidence: 99%
“…For example, since 1994, the Virtual Reality Modelling Language (VRML) has enabled the use of vector graphics to be deployed on the Web, supporting the creation of sharable 3D environments. VRML as a browser plug-in is a technology that is still actively used in a broad range of research applications, as demonstrated by Li et al (marine simulation [2]) and Yan et al (VR-based education systems [3]) and, within the art and cultures domain, Xiaobing et al employ the technology for ceramic painting and a fusion with virtual reality [4]. Hitherto, with 3D content being graphically heavy, scalability has been a longstanding limitation for widescale updates due to computational boundaries.…”
Section: Introductionmentioning
confidence: 99%